ANALISIS KORELASI PENDAPATAN DAERAH DENGAN PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI PROPINSI JAWA TENGAH - Joost, Gerard Albert (PRESTASI, 2014)
ABSTRACT.One of the main features in the region capable of carrying out regional autonomy is located on the fiscal capacity to finance the administration of the region with the degree of dependence on the central government has become smaller and the proportion is expected that the PAD should be the biggest part in mobilizing funds local governance. The problems examined in the study were (1) What is the relationship with the Regional Income Growth of Province of Central Java in 2003-2011? (2) What is the relationship with the Regional Special Allocation Fund Growth of Central Java province in 2003-2011? (3) What is the relationship of DBH with Economic Growth in Central Java province in 2003-2011? This study uses a quantitative approach. The sample was eight district / city of Central Java Province. The technique of sampling was purposive sampling, researchers took eight regencies / cities, among others: Purbalingga, Banjarnegara, Kebumen, Wonosobo district, Winton District, District Apex, Batang, Salatiga. The technique of collecting data through documentation. Data analysis techniques with panel data and analysis tools Least Square Dummy Variable (lSDV) or also known as Fixed Effect Model (FEM). using descriptive statistics and a different test (t-test). The results showed that there are significant fiscal decentralization in the province of Central Java is evidenced by (1) Local Revenue Local Revenue Estimate positive and significant impact on GDP with a significance level of 5%, where the value of the coefficient is equal to 2.654913 which means that if the revenue area increased 1 million, then the GDP will increase the amount of 2,654,913 dollars. (2) Special Allocation Fund Estimate of Special Allocation Fund and significant positive effect on GDP at 5% significance level where the value of the coefficient is equal to 6.916613 which means that if the special allocation fund increased by 1 million, then the GDP will increase the amount of 6,916,613 dollars. (3) DBH Tax / Non Tax Revenue Sharing Estimate Tax / Non-tax and no significant negative effect on GDP at 97% significance level 5 where the value of the coefficient is equal to 1.960468 which means that if the tax revenue / tax not increase 1 million, then the GDP will increase the amount of 1,960,468 dollars. (4) Based on the FEM model that generated the original income and the Special Allocation Fund and significant positive effect on GDP whereas DBH Tax and non-tax and no significant negative effect on GDP. Processing of data obtained from Chi-Sq value is 8.1507066 Statistics with Chi square table value at df (3) Î± = 5% is 7.81.Keywords: Regional Revenue, Economic Growth